ANALISIS USAHATANI KENTANG DI KECAMATAN KAYU ARO KABUPATEN KERINCI - Zuriana, Ema; Edison, Edison; Damayanti, Yusma (Universitas Jambi, 2019)
The purpose of this research is to analyze and cost production of potatoes farming at the Batang Sangir Village, Kayu Aro of District Kerinci Regency. This research used cost production analyze, received, provit and the farm avaible analyze bases on R/C ratio and modal productivity. From the research result we know that cost production of potatoes farming at the Kayu Aro of District was biggest for one season plants with wide average palnts 0,92 ha, need about RP.35.629.535/MT with average production KL 7.400/kg, super 4.520/kg and M 3.396/kg. The farming of potatoes is very profit. It show from the big result of potatoes farmer Rp.33.902.909/MT with profit is Rp.32.780.810/MT. The result of this research show that the farming of potatoes at the Batang Sangir village, Kayu Aro of District Kerinci Regency suitable to plants. Based on analyze of suitable to got value R/C Ratio is 1,95 â‰¥ 1. Itâ€™s mean is very increase cost is about Rp.1.000, that will got result about Rp.1.950. The productivity of capital employed amounted is 92 %. That mean biggest than Indonesia Bank Deposit rates prevailing on 2014 is 11%